Role of ligands in the formation, phase stabilization, structural and magnetic properties of alpha-Fe2O3 nanoparticles - Joshi, Satyawati S.; Patil, Prajakta R.; Nimase, Madhav S.; Bakare, P. P. (Journal of Nanoparticle Research, 2006)
The electrochemical synthesis of alpha Fe2O3 nanoparticles was performed using quaternary ammonium salts viz. TPAB, TBAB and TOAB in an organic medium by optimizing current density and molar concentration of the ligand. The role of ligands in the formation of alpha phase, structure and magnetic properties was investigated in details. The effect of increasing chain length on the particle size confirmed that as the chain length increases from propyl to octyl, the particle size decreases. X-ray diffraction spectra of as prepared samples and TEM analysis confirmed the amorphous nature of iron oxide. TEM showed beads of iron oxide joined together with a size distribution in the range of 6-30 nm. The Mossbauer studies also support this observation that for the lowest particle size, the line width is broader which successively reduces with increase in particle size. Iron oxide capped with TOAB indicated superparamagnetic nature at room temperature. The resultant internal magnetic field of 506 mm/s due to hyperfine splitting clearly established the formation of alpha-Fe2O3 The infrared spectroscopy and pH measurements revealed the binding of tetra alkyl ligand with iron oxide. The IR spectra and the increase in basicity of as prepared samples confirmed the formation of hydrated iron oxide. Above 800 degrees C the spectra indicated only iron oxide. Surface area obtained by BET method was 205 m(2)/g.
Keywords: Alkyl chain length; alpha-Fe2O3; Electrochemistry; magnetic properties; Nanoparticles; narrow size distribution